PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENCAPAI KETUNTASAN BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI SMAN 1 SUNGAI LALA INDRAGIRI HULU - Vidyastuti, Neni Nurlia Vidyastuti Nurlia; Amran, Elva Yasmi Amran Yasmi; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :TheResearch onthe application of learning model of guided inquiry has beendoneto achieve student’smastery learning on the subject of chemical equilibrium inclassXI SMAN1 Sungai Lala Indragiri Hulu. This researchis pra-experimentresearchwith one-shotstudy casedesign. The time of data collection was 01 November to 29 Novenber 2014.The sample was selected by the consideration of twoclasse of XI MIA, namely classXI MIA 1.The data analysis techniqueused the calculation of presentation of classicallearning mastery of knowledge competency, attitude competency and skill competency. The result of research was that classical learning mastery of knowledge competency is 92,59%. Then, the result of attitude competency and skill competency is 100%. Itmeans thatthe application oflearning model of guided inquiry can achieve student’smastery learning on the subject of chemical equilibrium inclassXISMAN1 Sungai Lala Indragiri Hulu. Keywords: Guided Inquiry, Mastery Learning, Chemical Equilibrium